Pengaruh Kompensasi Eksekutif Dan Efisiensi Operasional Terhadap Kinerja Keuangan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018 - Thesa Aulia; Erinos NR (Universitas Negeri Padang, 2020)
This study explain the effect of executive compensation and operational efficiency on the financial performance of banking company, which still unclear the effect of these variables. This study purposed to show and examine empirically the effect of executive compensation (X1), Non performing loan (X2), and Loan to deposit ration (X3) on financial performance banking company which measured by Return on asset (Y). the method that used in this study was causative comperative. The data which are used in this study were obtained from the banking company that listed in BEI in 2016-2018 and the sample were collected based on purposive sampling and resulted 117 companies. The result of this study showed that executive compensation has effect on ROA, while non performing loan has negative effect and significant on ROA, and Loan to deposit ratio has positive effect and significant on ROA. The next study expected to use another variables in order to get a better result and describe the variables which has effect on financial performance in company.